Photophysiological effects of UV induced mineral fluorescence on endolithic microalgae - Santos, Luísa Sarmento (2021)
Dinoflagellates of the family Symbiodiniaceae are microalgae best known for their importance as coral endosymbionts but they can also be found ex hospite, as free-living entities. Recently, it has been discovered that free-living cells in culture have the ability to produce an endolithic stage by precipitating calcium carbonate into mineral structures called symbiolites. This endolithic habitat is thought to protect the microalgae from UV radiation because the mineral absorbs UV light and emits less harmful blue mineral fluorescence. The fact that blue light is photosynthetically active radiation (PAR) led us to the hypothesis that mineral fluorescence could potentially influence the photosynthetic activity of the endolithic cells. To test this hypothesis, a Walz Microscopy-PAM was modified in order to expose cells to varying light conditions and analyse their photosystem II (PSII) fluorescence. Measurements under different light conditions showed distinct behaviors between free-living and endolithic cells and that, in the presence of UV, endolithic cells are exposed to more PAR light than free-living cells. With this modified system we were able to conclude that the UV did not cause any photodamage to the cells and that blue mineral fluorescence occurs and it has a positive effect on the photophysisology of endolithic cells, increasing their chances of survival and increasing their colonisable range in lower light environments.